2019
DOI: 10.1093/nar/gkz914
|View full text |Cite
|
Sign up to set email alerts
|

Controlling aggregation of cholesterol-modified DNA nanostructures

Abstract: DNA nanotechnology allows for the design of programmable DNA-built nanodevices which controllably interact with biological membranes and even mimic the function of natural membrane proteins. Hydrophobic modifications, covalently linked to the DNA, are essential for targeted interfacing of DNA nanostructures with lipid membranes. However, these hydrophobic tags typically induce undesired aggregation eliminating structural control, the primary advantage of DNA nanotechnology. Here, we study the aggregation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 75 publications
9
102
0
Order By: Relevance
“…The addition of a 6 nt overhang on cholesterol-tagged DNA strands has been postulated to assist during nanostructure assembly by inhibiting strand aggregation (Ohmann et al, 2019). We included a 6 nt overhang next to the cholesterol group on our dsDNA strand (dsDNA-6 nt) and observed a significant decrease in binding only on DPhPC liposomes.…”
Section: The Effect Of Solution Composition On Dna-liposome Colocalismentioning
confidence: 97%
See 2 more Smart Citations
“…The addition of a 6 nt overhang on cholesterol-tagged DNA strands has been postulated to assist during nanostructure assembly by inhibiting strand aggregation (Ohmann et al, 2019). We included a 6 nt overhang next to the cholesterol group on our dsDNA strand (dsDNA-6 nt) and observed a significant decrease in binding only on DPhPC liposomes.…”
Section: The Effect Of Solution Composition On Dna-liposome Colocalismentioning
confidence: 97%
“…The oligonucleotide sequences were generated using NUPACK design software (Zadeh et al, 2011) and selected to prevent the formation of unwanted secondary structures. The 6 nt 'overhang' sequence introduced at the 5' end of oligos was chosen from Ohmann, et al, 2019. Oligos were modified at the 3' end with a tetraethylene glycol cholesterol moiety (TEG-cholesterol) and with a 5' Alexa 647 fluorescent group respectively.…”
Section: Preparation Of Buffers and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This often eliminates structural control, which is the primary advantage of DNA nanotechnology. Addressing the issue of aggregation with cholesterol modification, Ohmann and coworkers recently showed that aggregation of ssDNA was sequence-dependent, whereas, in the self-assembled constructs, the position of the cholesterol modification was the dominant factor [63]. More importantly, the authors outlined the significant influence of particular bases (AAA bases had no aggregation) preceding the cholesterol modification and overhangs (six nucleotide overhangs on the complementary sequence) in suppressing aggregation.…”
Section: Fabrication With Organic Materialsmentioning
confidence: 99%
“…Cholesterol functionalization remains one of the most popular ways to anchor nucleic acid sequences with hydrophobic groups. These amphiphiles have the capacity to self-assemble into predictable morphologies (e.g., spherical micelles and vesicles) due to their tendency to microphase separate; these effects are dependent on the number of hydrophobic ligands, the type of residue and its position [ 61 , 62 , 63 ].…”
Section: Nucleic Acid Hybrid Nanocarriersmentioning
confidence: 99%